"Life is short, and art is long": RNA degradation in cyanobacteria and model bacteria. Issue 1 (24th March 2022) - Zhang, Ju‐Yuan; Hess, Wolfgang R.; Zhang, Cheng‐Cai
Abstract: RNA turnover plays critical roles in the regulation of gene expression and allows cells to respond rapidly to environmental changes. In bacteria, the mechanisms of RNA turnover have been extensively studied in the models Escherichia coli and Bacillus subtilis, but not much is known in other bacteria. Cyanobacteria are a diverse group of photosynthetic organisms that have great potential for the sustainable production of valuable products using CO2 and solar energy. A better understanding of the regulation of RNA decay is important for both basic and applied studies of cyanobacteria. Genomic analysis shows that cyanobacteria have more than 10 ribonucleases and related proteins in common with E. coli and B. subtilis, and only a limited number of them have been experimentally investigated. In this review, we summarize the current knowledge about these RNA‐turnover‐related proteins in cyanobacteria. Although many of them are biochemically similar to their counterparts in E. coli and B. subtilis, they appear to have distinct cellular functions, suggesting a different mechanism of RNA turnover regulation in cyanobacteria. The identification of new players involved in the regulation of RNA turnover and the elucidation of their biological functions are among the future challenges in this field.